1899 Ala. Laws 154 - (:unkn) unknown (My University, 1899)
Prohibited the discharge of any gun, pistol, or other firearm on a passenger train. Also prohibited reckless handling of any firearm or other weapon in the presence of other people on trains. Violators fined not less than one hundred nor more than five hundred dollars, or imprisoned not exceeding twelve months, or both at discretion of the court.
Keywords: DISCHARGE; HANDLING